KNOWLEDGE, ATTITUDES AND PRACTICES OF MACEDONIAN MOTHERS REGARDING PROBIOTIC USE IN CHILDREN - Ugrinoska Pandeva, Adrijana (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction: Probiotics are live microorganisms with documented benefits in preventing and treating pediatric illnesses, particularly those related to gastrointestinal health. Objective: To assess the level of knowledge, attitudes, and practices among Macedonian mothers regarding probiotic use in children. Methods: A cross-sectional study was conducted using a structured online questionnaire distributed to 527 Macedonian mothers through social media parenting groups. Results: 89.9% of respondents knew what probiotics are. 56% understood that probiotic formulations differ. 89.2% breastfed their babies and knew breast milk contains beneficial bacteria. 97.3% reported administering probiotics to their children. 64.1% gave probiotics after birth; 46.5% during breastfeeding. 71.6% administered probiotics concurrently with antibiotics. 65.1% noticed improvement in the child's health following probiotic use. Conclusion: Macedonian mothers exhibit a good level of awareness and engagement regarding probiotics. Their attitudes and practices align with current recommendations for the use of probiotics in pediatric care. Keywords: Probiotics, maternal knowledge, children, health behavior, Macedonia.